Nucleation during photoinduced spin-reorientation transition - Kovalenko, V.F.; Tychko, O.V. (Functional Materials, 2004)
Conditions of new magnetic phase nucleation during photoinduced spin-reorientation transition in homogeneously magnetized volume of doped yttrium-iron garnet are considered. The threshold densities of photoinduced uniaxial magnetic anisotropy and the corresponding critical linear dimensions of the nucleus are established depending on the material properties, magnetic anisotropy of initial state and irradiation conditions of the magnetically ordered medium. The limiting values of the mentioned threshold densities and minimum impurity concentrations defining the existence area of the photoinduced spin-reorientation transition in homogeneously magnetized volume of ferrite-garnets are determined. Рассмотрены условия образования зародыша новой магнитной фазы в процессе фотоиндуцированного спин-переориентационного перехода в однородно намагниченном объеме легированного иттрий железистого граната. Установлены значения пороговых плотностей энергии фотоиндуцированной одноосной магнитной анизотропии и соответствующие им критические линейные размеры зародыша в зависимости от свойств материала, магнитной анизотропии исходного состояния и условий облучения магнитоупорядоченной среды. Получены предельные значения упомянутых пороговых плотностей и минимальных концентраций примеси, ограничивающие область существования фотоиндуцированного спин-переориентационного перехода в однородно намагниченном объеме феррит гранатов. Розглянуто умови утворення зародка нової магнітної фази у процесі фютоіндукова-ного спін-переорієнтаційного переходу в однорідно намагніченому об’ємі легованого ітрій залізистого гранату. Встановлено значення порогових густин енергії фотоіндуко-ваної одновісної магнітної анізотропії і відповідні їм критичні лінейні розміри зародка в залежності від властивостей матеріалу, магнітної анізотропії вихідного стану і умов опромінення магнітоупорядкованого середовища. Отримано граничні значення згаданих порогових густин і мінімальних концентрацій домішки, що обмежують область існування фотоіндукованого спін-переорієнтаційного переходу в однорідно намагніченому об’ємі ферит-гранатів.